Energy Poverty, Practice, and Policy - Butler, Catherine (Progressive Energy Policy, 2022)
This Open Access book examines the implications of welfare policy for energy poverty and engages with key conceptual debates at the forefront of energy demand research. Academic work on energy poverty has rarely been brought into conversation with practice-theory-based approaches to energy use and sustainability. This book reveals how novel insights can be made visible through combining these different ways of thinking about energy demand issues. It presents a distinctive approach to energy poverty that places inequalities at the heart of debates about the advancing energy intensity of contemporary societies.